2018
DOI: 10.17161/kjm.v11i4.8707
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Health Medical Education Intervention and its Effects on Beliefs, Attitudes, Comfort, and Knowledge

Abstract: Introduction. Transgender health disparities have been well documented in the literature in recent years, as have the lack of transgender health issues in medical education programs across the country. Methods. A prospective study was conducted with an hour-long didactic lecture on transgender health being given to faculty, medical students, and residents at the University of Kansas School of Medicine-Wichita. The didactic lecture included educational information and presentations by transgender persons. A pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…A single educational intervention's outcomes were published, detailing a 1-hour didactic lecture for emergency department providers, including advanced practitioners. 19 Notably, this intervention was led by members of the transgender community. An immediate post-intervention survey of subjects noted that providers were more likely to (1) have increased consideration for transgender patients (49%), (2) increase screening for gender dysphoria among their patient base (22%), (3) continue their education around transgender medicine topics (16%), and (4) provide more treatment options for transgender patients (13%).…”
Section: Web-based Continuing Medical Educationmentioning
confidence: 99%
“…A single educational intervention's outcomes were published, detailing a 1-hour didactic lecture for emergency department providers, including advanced practitioners. 19 Notably, this intervention was led by members of the transgender community. An immediate post-intervention survey of subjects noted that providers were more likely to (1) have increased consideration for transgender patients (49%), (2) increase screening for gender dysphoria among their patient base (22%), (3) continue their education around transgender medicine topics (16%), and (4) provide more treatment options for transgender patients (13%).…”
Section: Web-based Continuing Medical Educationmentioning
confidence: 99%
“…As far as the authors are aware of there are no reports from India on this aspect. However recent reports have indicated that teaching program on LGBT health issues have been effective in significantly bringing about positive change in attitude, comfort level, and knowledge on LGBT health issues [20][21][22]. The most important observation of this pilot study was that the graduates who had studied bioethics had empathy clearly indicate the usefulness of teaching bioethics in the undergraduate curriculum and needs to be supported.…”
Section: Discussionmentioning
confidence: 78%
“…Third, while other evaluation tools determined a transphobia scale divided into domains such as knowledge, transphobia content, attitudes, belief, and so on, 13,32,34 this study evaluated only attitude and their change between before and after lecture using the GTS and ATTIS combined, indicating a lower value on the GTS and a higher value on ATTIS.…”
Section: Discussionmentioning
confidence: 99%